CULINARY TOURISM CENTER AND CREATIVE SPACE WITH GREEN ARCHITECTURE APPROACH - Riyadi, Ego; Hermawan, Hermawan; Hendriani, Adinda Septi (Clean Energy and Smart Technology, 2024)
The goal to be achieved from this planning is to Design a Culinary Tourism Center and Creative Space with a Green Architecture Approach by maximizing the existing land according to the concept taken. The limitations of this planning discussion are guided by the objectives and targets that have been set, namely the Design and Planning of a Culinary Tourism Center and Creative Space. Comparative studies are conducted to increase insight into similar building designs from several regions as a discourse in the Design and Planning of a Culinary Tourism Center and Creative Space with a Green Architecture Approach. The analysis was obtained from collecting data from the internet to support the Design and Planning process of a Culinary Tourism Center and Creative Space with a Green Architecture Approach. The Culinary Tourism Center and Creative Space is expected to become a new destination that is present as a combination of culinary tourism and creative space that answers our needs besides food, communal open spaces that function as a place for creativity, and encourage youth movements to be able to carry out healthy and collaborative activities. With the communal open space available, it will also become a place for creative people and their communities to channel their creativity, exchange ideas, and produce new creations without abandoning its architectural approach that minimizes harmful effects on human health and the environment.